Knowledge for Peace Transnational Justice and the Politics of Knowledge in Theory and Practice - Jones, Briony (Edward Elgar Publishing, 2021)
Combining the knowledge and experience of leading international researchers, practitioners and policy consultants, Knowledge for Peace discusses how we identify, claim and contest the knowledge we have in relation to designing and analysing peacebuilding and transitional justice programmes. Exploring how knowledge in the field is produced, and by whom, the book examines the research-policy-practice nexus, both empirically and conceptually, as an important part of the politics of knowledge production.